User perception regarding the use of the service in the program and free time of the secretary of sports and recreation of Itagui Colombia - Ramirez Perez, Edwin Alejandro (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
This research was developed in the city of Itagüí, it is a Municipality located in the south of the department of Antioquia-Colombia, the study that was carried out was cross-sectional, and it sought to know the user’s perception of the services provided by the sports entity of this city. The objective of this work was to determine the level of satisfaction of the users of the program "Leisure, free time and recreation" of the Secretariat of Sports and Recreation of Itagüí by means of the EPOD instrument of Nuviala (2008). This tool is made up of four dimensions, which were adapted to the environment, the scale was validated in its content by means of Cronbach’s Alpha with a value of 0.826. The best valued items were the technicians or instructors and activities. Among the great findings, it was shown that there is more participation of women than men in the programs offered by the Municipal entity.